Managerial decision making under uncertainty: the case of Twenty20 cricket - Sacheti, Abhinav; Gregory-Smith, Ian; Paton, David (SAGE, 2016)
We consider managerial decision making by examining the impact of decisions taken by cricket captains on Twenty20 International (T20I) match outcomes. In particular, we examine whether pressure from external commentators is associated with suboptimal decision making by captains. Using data from over 300 T20I matches, we find little evidence that either winning the toss or choosing to bat first improves the likelihood of winning. Despite this, we find that captains in T20I cricket are significantly more likely to choose to bat rather than bowl after winning the toss, a finding that is consistent with social pressure constraining captains’ decision making.